Intranasal premedication: special consideration in children - I Wayan Eka Arnawa (Intisari Sains Medis, 2018)
Introduction: Surgery in special population such as children may lead to emotional and physical stress. Premedication use may be beneficial in children anesthesia to reduce emotional stress and anxiety but still to be used in special consideration with adjustment dose. Intranasal premedication provides a broad effect of sedation and anti-anxiety and maybe produce a beneficial effect in child anesthesia.Aim: This study aimed to provide an overview regarding intranasal drugs and also intranasal premedication function in childrenConclusion: The intranasal application of pre-anesthetic drugs is the preferred route of administration and is an effective way to provide sedatives to children.